2018
DOI: 10.15761/nfo.1000197
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of intravitreal ranibizumab treatment on retinal ganglion cell complex and choroidal thickness

Abstract: Background: To evaluate the long-term effects of intravitreal ranibizumab treatment on both choroidal and retinal layers thicknesses using spectral domain optical coherence tomography (SD-OCT) and Enhanced Depth Imaging (EDI) mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…In a previous study conducted by Cakır et al,32 eyes in 27 patients with classic choroidal neovascularization who had undergone intravitreal 0.5 mg ranibizumab injections with a minimum of a 2-year follow up were enrolled as the study group. They reported that long-term IVR treatment was associated with significant reductions in the ganglion cell layer and internal plexiform layer thicknesses [25] . In another study, SFCT seemed to decrease after intravitreal bevacizumab injections in eyes with neovascular age-related macular degeneration as compared to untreated eyes with the same condition [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study conducted by Cakır et al,32 eyes in 27 patients with classic choroidal neovascularization who had undergone intravitreal 0.5 mg ranibizumab injections with a minimum of a 2-year follow up were enrolled as the study group. They reported that long-term IVR treatment was associated with significant reductions in the ganglion cell layer and internal plexiform layer thicknesses [25] . In another study, SFCT seemed to decrease after intravitreal bevacizumab injections in eyes with neovascular age-related macular degeneration as compared to untreated eyes with the same condition [26] .…”
Section: Discussionmentioning
confidence: 99%
“…5 Ganglion cell complex thickness (GCCT) plays a particularly important role in visual function and assessment of the visual field and has been analyzed in numerous in vitro and in vivo studies in humans and animals. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] This study aimed to analyze the relationship between GCCT and vision compared with choroidal thickness (CT) and central retinal thickness (CRT) in relation to the outcomes of intravitreal aflibercept treatment for choroidal neovascular membranes secondary to AMD.…”
Section: Introductionmentioning
confidence: 99%